Effect of cobalt-iron therapy on thyroid function - Tevetoğlu, Fethi (The Turkish Journal of Pediatrics, 1961)
We have studied the effect of a cobalt-iron preparation (Roncovite) on thyroid function in a group of anemic children. Neither clinical experience nor laboratory findings in these patients suggest any anti-thyroid effect from cobalt chloride administration. The findings of certain other investigators show a consistent reduction in thyroid function when cobalt is given. This tends to rule out idiosyncrasy as a factor in the purported goitrogenic action of cobalt. Two possible explanations are presented. Exacerbation or progression of a pre-existing thyroid dysfunction could occur independently during cobalt treatment for anemia. The presence of toxic impurities in some cobalt preparations could be involved. Pure cobalt chloride is not a goitrogen.